2015
DOI: 10.1093/europace/euv132
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulant therapy for stroke prevention in patients with atrial fibrillation undergoing ablation: results from the First European Snapshot Survey on Procedural Routines for Atrial Fibrillation Ablation (ESS-PRAFA)

Abstract: The European Snapshot Survey on Procedural Routines in Atrial Fibrillation Ablation (ESS-PRAFA) is a prospective, multicentre snapshot survey of patients undergoing atrial fibrillation (AF) ablation, conducted to collect patient-based data on current clinical practices in AF ablation in context of the latest AF Guidelines and contemporary oral anticoagulant therapies. The EP Research Network Centres were asked to prospectively enrol consecutive patients during a 6-week period (September/October 2014). Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…Currently, uninterrupted warfarin therapy is considered superior to interrupted anticoagulation strategy with respect to thromboembolic and bleeding complications [5–8]. Moreover, some studies, including our previous report [2], have evaluated the safety and efficacy of direct oral anticoagulants (DOAC) in the management of AF ablation [9–18]. However, the number of subjects analyzed in earlier studies is rather small.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, uninterrupted warfarin therapy is considered superior to interrupted anticoagulation strategy with respect to thromboembolic and bleeding complications [5–8]. Moreover, some studies, including our previous report [2], have evaluated the safety and efficacy of direct oral anticoagulants (DOAC) in the management of AF ablation [9–18]. However, the number of subjects analyzed in earlier studies is rather small.…”
Section: Introductionmentioning
confidence: 99%
“…Despite initial concerns on the safety of using periprocedural NOAC [20], nowadays, several large RCTs have demonstrated the safety and efficacy of uninterrupted use of NOACs (i.e., dabigatran, rivaroxaban, apixaban) during AF ablation [5,6,12] (Table 3). In clinical practice, however, most centers still use a minimally interrupted NOAC strategy [16]. The European Snapshot Survey on Procedural Routines in Atrial Fibrillation Ablation (ESS-PRAFA) in 2015 demonstrated that AF ablations were performed with a minimally interrupted NOAC strategy (1-2 doses withheld) in 53% of procedures, interrupted NOAC ≥2 days in 34%, and an uninterrupted NOAC strategy in 14% [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, the uninterrupted NOAC strategy does not reflect current clinical practice as most centers still use a minimally interrupted NOAC strategy [16]. There is limited data demonstrating the safety and efficacy of a minimally interrupted NOAC strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Warfarin, a vitamin K antagonist, has been commonly used as an oral anticoagulant during the periprocedural period of AF ablation. More recently, however, direct oral anticoagulants (DOACs) have been increasingly used for periprocedural anticoagulation therapy for AF ablation . At present, the following three perioperative DOAC anticoagulation strategies are used: uninterrupted (Unint; no discontinuation of DOACs), minimally interrupted (min‐Int; holding the morning dose on the day of ablation), and interrupted (holding doses > min‐Int holding dose).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, direct oral anticoagulants (DOACs) have been increasingly used for periprocedural anticoagulation therapy for AF ablation. 6 At present, the following three perioperative DOAC anticoagulation strategies are used: uninterrupted (Unint; no discontinuation of DOACs), minimally interrupted (min-Int; holding the morning dose on the day of ablation), and interrupted (holding doses > min-Int holding dose). The superiority among these three anticoagulation strategies in the periprocedural period of AF ablation, however, has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%